2012
DOI: 10.1517/17460441.2012.727394
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Pim1 structure for anti-cancer drug design

Abstract: To obtain a potent and selective Pim1 inhibitor as a lead compound, the authors propose the development of compounds which simultaneously interact with both the ATP binding site (Lys67, Glu121 and Phe49) and substrate binding residues (Asp128, Asp131 and Glu171). The development of Pim1 inhibitors could lead to new therapeutic options for a number of hematological malignancies and prostate cancer in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Our co-crystallography data revealed that 2′-HCA binds at the unique hinge region of Pim-1. This underscores the possibility of developing an effective therapeutic agent with high specificity for Pim-1 (39). …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our co-crystallography data revealed that 2′-HCA binds at the unique hinge region of Pim-1. This underscores the possibility of developing an effective therapeutic agent with high specificity for Pim-1 (39). …”
Section: Discussionmentioning
confidence: 90%
“…To determine how 2′-HCA specifically targets Pim-1, we used structural biology approaches. Pim-1 is functionally and structurally different from other classes of kinases (39), and has a unique hinge region sequence as well as novel hinge architecture (40). Our co-crystallography data revealed that 2′-HCA binds at the unique hinge region of Pim-1.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, structurally diverse small‐molecule inhibitors have continued to be developed for regulation of Pim kinase activity both as research tools and drug candidates 2e. 3, 4 More than 400 small‐molecular Pim‐1 inhibitors with K i (IC 50 ) values <10 μ M have been registered in the ChEMBL database 3…”
Section: Methodsmentioning
confidence: 99%
“…Other kinases additionally form a hydrogen bond between the N1 atom of adenine and the backbone NH of the third hinge residue. The proline residue at position 123 in Pim‐1 precludes the kinase from this capability 3. In the present study, this distinctness in the protein structure was used for the construction of selective bisubstrate inhibitors, ARC(PIM) compounds.…”
Section: Methodsmentioning
confidence: 99%
“…All the above-mentioned compound classes showed acceptable IC 50 values toward Pim kinases (below 10 nmol/L in some cases, see Table 1). The ATP-binding pocket, along with the substrate-recognition residues are identified as crucial for Pim kinase inhibitors (19).…”
Section: Introductionmentioning
confidence: 99%